The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1101/2023.04.25.538339
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Performance of qpAdm-based screens for genetic admixture on admixture-graph-shaped histories and stepping-stone landscapes

Abstract: Although a broad range of methods exists for reconstructing population history from genome-wide single nucleotide polymorphism data, just a few methods gained popularity in archaeogenetics: principal component analysis (PCA); ADMIXTURE, an algorithm that models individuals as mixtures of multiple ancestral sources represented by actual or inferred populations; formal tests for admixture such as f3-statistics and D-statistics; and qpAdm, a tool for fitting two-component and more complex admixture models to grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 77 publications
(338 reference statements)
0
10
0
Order By: Relevance
“…e . after the time of the ancient individual(s) 49 . The most principled approach is thus to build ancestry models where source and ‘outgroup/reference’ populations are older than, or at least contemporary with, the target genome or group which we are trying to model 49 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…e . after the time of the ancient individual(s) 49 . The most principled approach is thus to build ancestry models where source and ‘outgroup/reference’ populations are older than, or at least contemporary with, the target genome or group which we are trying to model 49 .…”
Section: Resultsmentioning
confidence: 99%
“…Modern populations provide ample power to detect differences, but their genetic affinity to ancient individuals may be confounded by later gene flow, i.e. after the time of the ancient individual(s) 49 . The most principled approach is thus to build ancestry models where source and 'outgroup/reference' populations are older than, or at least contemporary with, the target genome or group which we are trying to model 49 .…”
Section: Northern Europementioning
confidence: 99%
See 1 more Smart Citation
“…Following results from our ADMIXTURE and PCA analyses, we included multiple Asian and Melanesian populations (limited to a subset of Papuan language speakers; see SI Methods) as potential ancestry sources, and added the Toalean forager and Onge population as proxies for founder ancestry. To improve qpAdm sensitivity and power, we rotated populations across 'left' and 'right' groupings to produce a large set of ancestry models for each Wallacean population that were evaluated for plausibility (see SI Methods; (39)).…”
Section: Evidence For Retention Of Amh Founder Ancestry In Wallaceamentioning
confidence: 99%
“…However, sifting through all possible proxy sources and the right populations for an admixture event can be overwhelming. In addition, a recent survey has shown that, depending on the approach and the quality of the genetic data analyzed, qpAdm may suffer from high false discovery rates, adding substantial uncertainty to the interpretation of the results of admixture inference (Eren Yüncü et al, 2023).…”
Section: Introductionmentioning
confidence: 99%